KEMAMPUAN MAHASISWA PGSD FKIP UR DALAM KETERAMPILAN MEMBACA PEMAHAMAN - Munjiatun Munjiatun; Otang Kurniaman; Ulil Meisal (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
Research constitutes research by use of quantitative with arranges instrument to essay as collector of ability data reads comprehension. Total sample on observational 175 consisting of person three PGSD FKIP UR college student generation, one that is seen on ability reads generation grasp 2014 by average 67,66, generation 2013 by average ability read 64,39, and ability reads generation 2014 by average 72,69. Seen from tall category 2 person with percentage 1,14%, enough category by totals 124 by percentages 70,86%, and low category 49 person with percentage 28% afterses at accounts statistic's ala therefore available distinctive signifikan's ones ability reads PGSD FKIP UR college student grasp. To clearer again therefore will work through perindikator that builds to read grasp, one that will beforehand word on intrinsik's elemental indicator is seen on a par ability reads for generation 2014 by average 71,03, generation 2013 as big as 67,42, and for generation 2014 as big as 77,63. To see ability category read grasp on intrinsik's elemental indicator that get tall category with percentage 13,71% by total 24 college students, enough category with percentage 72% by total 126 college students, and low category with percentage 14,28% by total 25 college students, to see the difference therefore at quiz utilizes Chi square therefore available difference which signifikan among ability reads PGSD FKIP UR college student grasp on intrinsik's elemental indicator. Indicator second about sentence of college student amount 175 person that get tall category 4 person with percentage 2,29%, enough category 67 person with percentage 38,29%, and low category 104 person with percentage 59,43%, seen on average ability read grasp on indicator generation college student sentence 2014 by average 64,29, generation 2013 by average 61,36, and generation 2012 by average 67,76, after at quiz utilizes Chi-square therefore no difference signifikan's one ability reads PGSD FKIP UR college student grasp on indicator sentence.Keywords: comprehension reading